2000
DOI: 10.1046/j.1523-1755.2000.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerivastatin prevents angiotensin II-induced renal injury independent of blood pressure- and cholesterol-lowering effects

Abstract: Cerivastatin reduced inflammation, cell proliferation, and iNOS induction, which led to a reduction in cellular damage. Our findings suggest that 3-hydroxy-3-methylglutaryl coenzyme (HMG-CoA) reductase inhibition ameliorates Ang II-induced end-organ damage. We suggest that these effects were independent of cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 42 publications
7
105
0
2
Order By: Relevance
“…[1][2][3] Therefore, the ability of statins to inhibit ICAM-1 expression indicates that statins can attenuate leukocyte-endothelial cell interactions and the subsequent endothelial damage and tissue injury. Indeed, many studies have reported that statins can inhibit leukocyte-endothelial cell interactions in many conditions, such as thrombin-activated leukocyte-endothelial cell interactions, 47 angiotensin II-induced injury, 35,48 transient ischemic injury, 36,49 and Staphylococcus aureus ␣-toxin-induced inflammation. 14 These results provide the best evidence to support the view that statins can inhibit leukocyte-endothelial cell interactions independent of their lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Therefore, the ability of statins to inhibit ICAM-1 expression indicates that statins can attenuate leukocyte-endothelial cell interactions and the subsequent endothelial damage and tissue injury. Indeed, many studies have reported that statins can inhibit leukocyte-endothelial cell interactions in many conditions, such as thrombin-activated leukocyte-endothelial cell interactions, 47 angiotensin II-induced injury, 35,48 transient ischemic injury, 36,49 and Staphylococcus aureus ␣-toxin-induced inflammation. 14 These results provide the best evidence to support the view that statins can inhibit leukocyte-endothelial cell interactions independent of their lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][47][48][49] These differences may derive from the diversity of the mechanisms of each model or duration of the drug administration. In addition, many studies with streptozotocin-induced diabetic animals were performed for a relatively short duration compared to chronic diabetes in human.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with superoxide dismutase (SOD) reduced spontaneous tone of aorta isolated from rats infused with ANG II (39) and SOD (19) or SOD mimetic (29,30) blunted hypertension induced by ANG II in rats. Inhibition of the HMGCoA reductase with various statins was reported to reduce arterial pressure and to prevent cardiac hypertrophy and renal injury in models of ANG II-dependent hypertension (31,45). A link between ANG II-induced generation of oxygen radicals and cellular hypertrophy was demonstrated in aortas of mice genetically deficient in gp91 phox (40) and in mouse renal tubular cells transfected with p22 phox antisense (16), two membrane-bound NADPH oxidase subunit proteins.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Rats were purchased from RCC Ltd (Fuellinsdorf, Switzerland). Experiments were conducted in 4-week-old male dTGR (nϭ28) and nontransgenic, age-matched Sprague-Dawley (SD; Tierzucht Schoenwalde, Germany; nϭ7) rats after due approval (permit No.…”
Section: Animal Groups and Physiological Measurementsmentioning
confidence: 99%